2012
DOI: 10.1038/npp.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Selective DNA Methylation of BDNF Promoter in Bipolar Disorder: Differences Among Patients with BDI and BDII

Abstract: The etiology of bipolar disorder (BD) is still poorly understood, involving genetic and epigenetic mechanisms as well as environmental contributions. This study aimed to investigate the degree of DNA methylation at the promoter region of the brain-derived neurotrophic factor (BDNF) gene, as one of the candidate genes associated with major psychoses, in peripheral blood mononuclear cells isolated from 94 patients with BD (BD I ¼ 49, BD II ¼ 45) and 52 healthy controls. A significant BDNF gene expression downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 71 publications
5
110
1
1
Order By: Relevance
“…Although DNA methylation shows significant between-tissue variation, some interindividual differences in DNA methylation are correlated across brain and blood of healthy subjects (33), suggesting that epigenetic profiling of peripheral tissue may be useful for studies of brain disorders. Consistent with this hypothesis, DNA methylation changes have been found both in psychiatric postmortem brain samples (34,35) and in peripheral blood of the living psychiatric patients (12)(13)(14). However, a challenge to this field of study is whether epigenetic markers in peripheral tissues can predict functionally relevant epigenetic changes in the brain and consequent behavioral and psychiatric outcomes.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although DNA methylation shows significant between-tissue variation, some interindividual differences in DNA methylation are correlated across brain and blood of healthy subjects (33), suggesting that epigenetic profiling of peripheral tissue may be useful for studies of brain disorders. Consistent with this hypothesis, DNA methylation changes have been found both in psychiatric postmortem brain samples (34,35) and in peripheral blood of the living psychiatric patients (12)(13)(14). However, a challenge to this field of study is whether epigenetic markers in peripheral tissues can predict functionally relevant epigenetic changes in the brain and consequent behavioral and psychiatric outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies suggested that concentrations of BDNF protein in the blood (serum or plasma) may represent peripheral manifestation of depression (48) and schizophrenia (49) and could be used as a biomarker for therapeutic efficacy (50). Similarly, BDNF DNA methylation changes have been found in the peripheral blood of patients suffering from depression (13), bipolar disorder (12), schizophrenia (14), and eating disorders (51), and a change in BDNF DNA methylation status correlated with a positive response to psychotherapy in borderline personality disorder (52). In addition, within a psychiatric population, high BDNF DNA methylation was strongly associated with the history of child maltreatment (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next we examined genome-wide variation between the saliva and blood sample sets in genomic regions annotated to the following features: proximal promoters (2 kb upstream of RefSeq genes), RefSeq genes, coding sequences (CDS), LINEs (L1 and L2), SINEs (Alu), previously reported mental disorder-associated genes found by DNA methylation studies using peripheral tissue (BDNF, SLC6A4, CACNA1C, HTR1A, COMT, ST6GALNAC1, DRD2, and GAD1) [8,[67][68][69][70][71][72][73][74][75], and the above described DMWs. A box whisker plot of read counts in the grouped datasets at each genomic feature and a matching line graph for the individual datasets (normalized and summarized) showed a very similar profile with little variability and inter-individual difference, with DMWs as the natural exception ( Figure 4A,B).…”
Section: Comparable Dna Methylation Patterns Between Blood and Salivamentioning
confidence: 99%
“…Dunham et al 121 showed decreased expression of hippocampal BDNF and its receptors in patients with BD and major depression. The studies of Rao et al 122 and D'Addario et al 123 suggest that changes in BDNF levels in BD patients are linked to epigenetic changes, such as hypo-and hypermethylation of DNA regions associated with BDNF expression. Additionally, histone deacetylases (HDAC) have been described as a potentially promising target for treatment of several neurological disorders.…”
Section: Animal Models Of Bipolar Disordermentioning
confidence: 99%